The Factors Influencing Students’ Performance in Chemistry in Selected Senior High Schools - Yaayin, Boniface; Kamboke, Mathilda (Journal of Multidisciplinary Research and Development, 2025)
This study examined the factors influencing students' academic performance in chemistry at selected senior high schools in Kassena-Nankana Municipality, Ghana. A quantitative research method, rooted in the positivist paradigm, which assumes the existence of a single objective reality and excludes subjective values was utilised in this study. Therefore, it relied on numerical data to achieve objectivity. A descriptive correlational research design was used as a blueprint for the quantitative data collection and analysis. This design establishes the degree of influence or relationship between the variables understudy using statistical analysis. The study involved 140 participants, selected from an accessible population of 279 third-year students across four senior high schools, using purposive and simple random sampling. Data collection instruments included test and a questionnaire, which was designed in a form of a five-point Likert scale. The findings indicate that teacher quality, classroom environment, and teaching and learning resources had negative influence on students' performance in chemistry. Consequently, regression analysis revealed that all three factors: Teacher quality, classroom environment and teaching and learning resources significantly negatively influenced students’ academic performance in chemistry across the selected schools that were engaged in this study. The study thus concludes that among the selected schools considered for this study; teacher quality, classroom environment and teaching and learning resources are contributory factors to students’ low performance in chemistry. It is therefore recommended that continuous professional development for chemistry teachers in the selected schools should be institutionalised by leadership of the schools to enhance students’ learning outcomes in chemistry.